2004
DOI: 10.1111/j.1471-4159.2004.02793.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of A2B adenosine receptor functioning by tumour necrosis factor a in human astroglial cells

Abstract: Low-affinity A 2B adenosine receptors (A 2B ARs), which are expressed in astrocytes, are mainly activated during brain hypoxia and ischaemia, when large amounts of adenosine are released. Cytokines, which are also produced at high levels under these conditions, may regulate receptor responsiveness. In the present study, we detected A 2B AR in human astrocytoma cells (ADF) by both immunoblotting and real-time PCR. Functional studies showed that the receptor stimulated adenylyl cyclase through Gs proteins. Moreo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 36 publications
4
63
0
Order By: Relevance
“…Together, these data suggest that TNF-␣ and probably some other inflammatory cytokines promote A 2A R signaling and function through multiple effects, not only enhancing the receptor number but also regulating mediators of receptor signaling and desensitization. Our demonstration that TNF-␣ inhibits A 2A R desensitization is also consistent with the previous report by Trincavelli et al (2004) that TNF-␣ inhibits desensitization of A 2B Rs and enhances the functions of these receptors in human astroglial cells. Moreover, the current study provides further mechanistic insight into TNF-␣-mediated inhibition of receptor desensitization.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Together, these data suggest that TNF-␣ and probably some other inflammatory cytokines promote A 2A R signaling and function through multiple effects, not only enhancing the receptor number but also regulating mediators of receptor signaling and desensitization. Our demonstration that TNF-␣ inhibits A 2A R desensitization is also consistent with the previous report by Trincavelli et al (2004) that TNF-␣ inhibits desensitization of A 2B Rs and enhances the functions of these receptors in human astroglial cells. Moreover, the current study provides further mechanistic insight into TNF-␣-mediated inhibition of receptor desensitization.…”
Section: Discussionsupporting
confidence: 81%
“…Although GRK2 and other GRKs are regulated by both endogenous and exogenous factors (Penela et al, 2003), there has been some evidence that expression and activity of GRKs are regulated by inflammation and inflammatory cytokines in certain cells or tissues (Lombardi et al, 1999(Lombardi et al, , 2001). More recent studies by Trincavelli et al (2004) demonstrated that TNF-␣ reduced agonist-dependent receptor phosphorylation and attenuated agonist-mediated desensitization of A 2B Rs in human astroglial cells. Precise mechanisms of TNF-␣ regulation of adenosine receptor desensitization and the role of this cytokine in regulation of GPCR activity in general, however, remain unknown.…”
mentioning
confidence: 99%
“…These transcription factors drive GFAP upregulation and cell proliferation [22,78,79,80]. The PKB/Akt system 2) [61]. A similar convergence on STAT transducers is operated by the Janus family kinases (JAK) in response to extracellular GFs and cytokines including the astrogliosis triggers IL6, CNTF, EGF, and TGFα (Fig.…”
Section: Intracellular Transduction Pathways and Cellular Reactivitymentioning
confidence: 99%
“…Indeed, a regulatory connection between inflammatory cytokines,Ado and its receptors has been demonstrated in astrocytes grown in vitro. For example, exposure to the astrogliosis-promoting agent TNF reduced the internalization and down-regulation of the A2B receptor subtype [61].…”
Section: Cytokines and Growth Factorsmentioning
confidence: 99%
“…TNF-α has been shown to interact with adenosine in its effects during hypoxia. Very little is known about this interaction [49,50]. Hypoxia induces oxidative stress in the brain [51,52] and is associated with increased levels of proinflammatory cytokines, such as TNF-α in pig [53], in humans [54] and in mice [55].…”
Section: Tnf-α and Hypoxia In The Cnsmentioning
confidence: 99%